Docosanol and docosanol-mediated synthesis of gold nanoparticles target biofilm formation in drug resistant pathogens - Judan Cruz, K. G. (International Journal of Agricultural Technology, 2024)
An emerging approach in the design of novel antimicrobial drugs to control pathogenesis is through targeting biofilm formation in bacteria. Biofilm formation is a quorum sensing-linked virulence factor that plays a major role in the development of antibiotic resistance. The research findings highlighted the action of a bioactive compound Docosanol and Docosanol gold nanoparticles on the inhibition of biofilm formation against drug-resistant pathogens, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumoniae. The successful synthesis of gold nanoparticles using Docosanol was confirmed through characterization such as change in solution color to pink, UV–visible spectra peak at 550 nm and DLS analysis that showed particle mean size at 48.3 nm + 2.1 nm. Significantly lower biofilm formation was noted using Docosanol against all test bacterial pathogens. Docosanol-AuNPs showed higher biofilm formation inhibition in S. aureus and P. aeruginosa compared to Docosanol alone. This study emphasized the potential of Docosanol and Docosanol-AuNPs in developing strategies against biofilm formation, microbial pathogenesis and resistance